علوم عصریہ کی نصابی تشکیل نو : اسلامی فلسفہ تعلیم کے تناظر میں تطبیقی مطالعہ: Revising the Curriculum of Contemporary Sciences: An Applied Study in the Islamic Philosophy of Education - Umer yousaf; Dr. Allah Ditta (AL-IDRAK JOURNAL, 2024)
This study examines the revision of curricula in contemporary sciences through the lens of Islamic philosophy of education, emphasizing the integration of spiritual and moral dimensions with modern academic disciplines. In an age dominated by secular educational paradigms, the disconnect between material and spiritual knowledge has led to a fragmented understanding of human development. This paper explores how Islamic educational philosophy, with its holistic and balanced approach, can address this issue by harmonizing the Qur'anic worldview with the advancement of modern sciences. The research delves into principles derived from classical Islamic thought, such as the unity of knowledge, the role of ethics, and the integration of 'aql (reason) and naql (revealed knowledge). It analyzes how these principles can be applied practically to restructure curricula in fields like medicine, technology, and social sciences, fostering a generation equipped with intellectual competence and spiritual wisdom. Through a comparative and applied methodology, the paper highlights existing models and proposes actionable frameworks for curriculum redesign.This applied approach aims to bridge the gap between traditional Islamic epistemology and contemporary academic demands, ensuring a comprehensive development of individuals and societies in line with Islamic ideals.